Reduction of torque ripple in DTC for induction motor using input-output feedback linearization, ISSN 1303-6203 - Sebti Belkacem; Naceri Farid (Turk Journal of Electrical Engineering and computer Sciences, 2013)
Direct torque control (DTC) is known to produce fast responses and robust control in AC adjustable-speed drives. However, in the steady-state operation, notable torque, ﬂux, and current pulsations occur. In this paper, nonlinear DTC of induction motor drives is presented based on a space vector pulse-width modulation scheme combined with the input-output feedback linearization technique. The variation of stator and rotor resistance due to changes in temperature or frequency deteriorates the performance of the DTC controller by introducing errors in the estimated ﬂux linkage and the electromagnetic torque. This approach will not be suitable for high power drives such as those used in tractions, as they require good torque control performance at a considerably lower frequency. Finally, extensive simulation results are presented to validate the proposed technique. The system is tested at diﬀerent speeds and a very satisfactory performance is achieved.